EVALUASI TINGKAT KEPATUHAN PENGGUNAAN OBAT ANTIHIPERTENSI PADA PASIEN PENYAKIT GINJAL KRONIK LANJUT USIA - Fajriansyah Fajriansyah; Michrun Nisa (Jurnal Ilmiah Manuntung, 2017)
Chronic Kidney Disease (CKD) is a condition of kidney damage that occurs for 3 months or more in the form of structural or functional abnormalities of the kidney with or without decrease in Glomerular Filtration Rate which manifests as a pathological disorder. Treatment of CKD is closely related to medication adherence that determines a successful treatment, but patient treatment adherence is often low especially in regularity for drug use. This study aims to evaluate the level of adherence to the use of CKD patient drug at the General Hospital of Education Hasanuddin University. The research design is descriptive analysis with Cross Sectional. The data were collected by using questionnaires containing questions that led to patient characteristics, medication adherence, and factors affecting drug use. Measurement of adherence used is Modified Morisky Scale (MMS) which then analyzed using Case Management Adherence Guidelines (CMAG) against 45 subjects. The result of the research is the level of patient compliance based on quadrant level 1 as many as 8 patients (17,78%), quadrant level 2 as many as 8 patient (17,78%), level 3 quadrant 17 patient (37,77%), and quadrant level 4 of 12 patients (26.66%).